Efficacy of a Homeopathic Complex (Masta-forte+Actino Cure) and Antibiotics in Treatment of Bovine Clinical Mastitis - Parsani, H. R.; Shyma, K. P.; Patel, J. A.; Chaudhary, N. R.; Patel, M. K. (International Journal of Bio-resource and Stress Management, 2023)
The present study was aimed to treat bovine mastitis with homeopathic remedies Masta-forte+Actino Cure along with antibiotic therapy. A total 160 animals suffering from clinical bovine mastitis were used for study. All the animals were categories according to their physical condition of udder as redness, oedematous, fibrosis, bloody milk, white clot in milk, and watery milk. All the animals were group in to two groups A (n=80) and (n=80). All the animals were basically treated with higher antibiotics. In group A animal were treated with homeopathic medicine (2 ml. Masta-Forte+2 ml Actino Cure) orally with syringe bid for 20 days along with antibiotic therapy were as group B only treated with antibiotic therapy. Out of 160 animals 124 animals recovers with reduce normal milk. Among group A animals were recovery rate 90.00% (N=80) where as group B recovery rate 65.00% (n=80) animal. In group A animals having no fibrosis, where in group B animals having affected quarters were hard and fibrotic in nature. Homoeopathy drugs may be used as alternate therapy in organic farming system might be one of the preferred treatment methods.